Extracting Money from Causal Decision Theorists. - Oesterheld, Caspar; Conitzer, Vincent (Philosophical Quarterly, 2021)
Newcomb's problem has spawned a debate about which variant of expected utility maximisation (if any) should guide rational choice. In this paper, we provide a new argument against what is probably the most popular variant: causal decision theory (CDT). In particular, we provide two scenarios in which CDT voluntarily loses money. In the first, an agent faces a single choice and following CDT's recommendation yields a loss of money in expectation. The second scenario extends the first to a diachronic Dutch book against CDT.